Rationale behind IPO underpricing: evidence from Asian REIT IPOs - Ooi, Joseph T.L.; Mori, Masaki; Wong, Woei Chyuan (John Wiley & Sons, Inc., 2018)
This article examines the rationale behind IPO underpricing using a sample of REIT IPOs in Asia. Although the IPOs registered an average initial return of 3.08%, the issuers were able to sell the IPO shares above their fundamental values by timing the listings in periods when existing REIT stocks are traded at a premium to their net asset values (NAV). An IPO could therefore be underpriced and yet produce a net gain for the issuer. The issuers’ net gain from IPO is, however, negatively related to long‐run performance of REIT IPOs.